1998
DOI: 10.1016/s0042-6989(98)00025-x
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the timing of human analysis of motion and chromatic signals from occipital to temporo-parieto-occipital cortex: A transcranial magnetic stimulation study

Abstract: In human visual analysis, the initial processing of motion and chromatic signals may be mediated by feed-forward pathways from striate cortex to segregated areas of extrastriate cortex. The time-course of occipital to temporo-parieto-occipital motion processing was unknown, as was the selectivity of the effect of transcranial magnetic stimulation (TMS) on motion processing. TMS delivered over occipital cortex degraded the discrimination of motion-defined form (MDF) in a discrete time window beginning 100-120 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 52 publications
2
16
2
Order By: Relevance
“…Finally, it is also possible that TMS will act on both parameters (x-intercept and slope), inducing a leftward shift and an increase in slope. It is important to note that in all these cases, the y-intercept (the threshold when no noise has been added to the stimulus) will increase, which is consistent with the general observation that TMS interferes with perceptual sensitivity, such as has been shown for motion direction discriminations when TMS is applied over V5/MT (Anand et al 1998;Beckers and Homberg 1992;Beckers and Zeki 1995;Hotson et al 1994;Hotson and Anand 1999;Matthews et al 2001;Sack et al 2006). …”
supporting
confidence: 76%
“…Finally, it is also possible that TMS will act on both parameters (x-intercept and slope), inducing a leftward shift and an increase in slope. It is important to note that in all these cases, the y-intercept (the threshold when no noise has been added to the stimulus) will increase, which is consistent with the general observation that TMS interferes with perceptual sensitivity, such as has been shown for motion direction discriminations when TMS is applied over V5/MT (Anand et al 1998;Beckers and Homberg 1992;Beckers and Zeki 1995;Hotson et al 1994;Hotson and Anand 1999;Matthews et al 2001;Sack et al 2006). …”
supporting
confidence: 76%
“…Consistent with monkey electrophysiology (see Born and Bradley, 2005) and human neuroimaging (see Orban et al, 2003), several TMS studies (Beckers and Zeki, 1995;Anand et al, 1998;Walsh et al, 1998;Hotson and Anand, 1999;Silvanto et al, 2005;Sack et al, 2006;Laycock et al, 2007) have shown that hMT/V5ϩ plays a key role in visual-motion processing. TMS of this region also affects visuomotor coordination: it reduces the spatial accuracy of reaching to stationary objects after adaptation to background motion (Whitney et al, 2007), and the movement speed to catch horizontally moving targets (Schenk et al, 2005).…”
Section: Discussionmentioning
confidence: 56%
“…Previous online TMS studies on the role of V1 in motion perception have typically found a single, broad (Anand et al, 1998;Hotson and Anand, 1999) or a single narrow period (Beckers and Zeki, 1995;Laycock et al, 2007) of V1 activity. Only Silvanto et al (2005b) and the current study have found evidence for distinct early and late periods of V1 activity (although such evidence has been obtained in other domains such as figure-ground segregation; Heinen et al, 2005).…”
Section: Discussionmentioning
confidence: 99%